Super-Earth of 8 M[Earth] in a 2.2-day orbit around the K5V star K2-216 - Persson, Carina M.; Heeren, Paul (Astronomy and astrophysics, 2018)
Although thousands of exoplanets have been discovered to date, far fewer have been fully characterised, in particular super-Earths. The KESPRINT consortium identified K2-216 as a planetary candidate host star in the K2 space mission Campaign 8 field with a transiting super-Earth. The planet has recently been validated as well.Aims. Our aim was to confirm the detection and derive the main physical characteristics of K2-216 b, including the mass.Methods. We performed a series of follow-up observations: high-resolution imaging with the FastCam camera at the TCS and the Infrared Camera and Spectrograph at Subaru, and high-resolution spectroscopy with HARPS (La Silla), HARPS-N (TNG), and FIES (NOT). The stellar spectra were analyzed with the SpecMatch-Emp and SME codes to derive the fundamental stellar properties. We analyzed the K2 light curve with the pyaneti software. The radial velocity measurements were modelled with both a Gaussian process (GP) regression and the so-called floating chunk offset (FCO) technique to simultaneously model the planetary signal and correlated noise associated with stellar activity.Results. Imaging confirms that K2-216 is a single star. Our analysis discloses that the star is a moderately active K5V star of mass 0.70 ± 0.03 M⊙ and radius 0.72 ± 0.03 R⊙. Planet b is found to have a radius of R⊕ and a 2.17-day orbit in agreement with previous results. We find consistent results for the planet mass from both models: Mp ≈ 7.4 ± 2.2 M⊕ from the GP regression and Mp ≈ 8.0 ± 1.6 M⊕ from the FCO technique, which implies that this planet is a super-Earth. The incident stellar flux is F⊕.Conclusions. The planet parameters put planet b in the middle of, or just below, the gap of the radius distribution of small planets. The density is consistent with a rocky composition of primarily iron and magnesium silicate. In agreement with theoretical predictions, we find that the planet is a remnant core, stripped of its atmosphere, and is one of the largest planets found that has lost its atmosphere.